Some questions of historical metrology of the Balkars and Karachays - Elena G. Muratova (Кавказология, 2023)
The article is devoted to the study of some issues of historical metrology of the Karachay-Balkars, inextricably linked with their economic activity, which occurred in the mountainous conditions of the Central Caucasus. This article contains examples of used length, volume and square measurement units in the Karachay-Balkars’ traditional metrology, found in historical records. It is shown that it is necessary to start research on the socio-economic history of Balkaria in the 19th century from the study of historical metrology. The system of weights and measures was necessary for a clear regulation of feudal duties, “payment for blood” and wedding payments. But firstly, it was determined by the specifics of the economic activity of the people.The most common way to measure volume was to determine it through the capacity of a vessel. The name of the vessel was transferred to the name of the measure. Volumetric and approximate units of measurement were widely used: “cart”, “arba”. Mountainous relief determined the use of such length measurement units as the distance of “hearing one cry” or “accessible to human vision.” The measure of the area of the land plot was or the labor costs for cultivating the land, or the volume of grain sown, or the volume of the harvest. The most commonly used crop measure was the mountain shock, «gorskaya kopna». This metric gradually obtained a meaning associated with the tithe. Mowed lands were estimated by the volume of hay harvested, and pastures by the number of livestock that could be kept on them.